2020
DOI: 10.2196/17163
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Health Literacy and Social Support and the Quality of Life in Patients With Cancer: Questionnaire Study

Abstract: Background Low health literacy is associated with factors such as not taking medication as prescribed as well as poor health status and increased hospitalization and mortality risk, and has been identified as a risk factor for decreased physical function in older individuals. Health literacy is becoming an increasingly important issue because of the increased number of people affected by cancer who must make complicated treatment decisions. Health literacy has been shown to be positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 55 publications
(57 reference statements)
4
26
1
1
Order By: Relevance
“…Although not explicitly expressed by the professionals in our study, an overestimation of patients' HL levels could explain the struggle of professionals to convey health information to patients. Inviting family members to co-produce health and care might compensate for patients' low levels of HL [61] and improve patients' quality of life [62]. However, our findings mirror those from a study in the US Veterans' Health Administration that suggest that family members want to participate in health and care decisions with and for patients with HF but feel excluded from care teams [63].…”
Section: Individual and Relational Factors Influencing Co-productionsupporting
confidence: 58%
“…Although not explicitly expressed by the professionals in our study, an overestimation of patients' HL levels could explain the struggle of professionals to convey health information to patients. Inviting family members to co-produce health and care might compensate for patients' low levels of HL [61] and improve patients' quality of life [62]. However, our findings mirror those from a study in the US Veterans' Health Administration that suggest that family members want to participate in health and care decisions with and for patients with HF but feel excluded from care teams [63].…”
Section: Individual and Relational Factors Influencing Co-productionsupporting
confidence: 58%
“…In this study, anxiety and depression were negatively correlated with PSS, and PSS was positively correlated with quality of life, consistent with previous findings [49,50]. PSS moderates the effects of anxiety or depression on quality of life of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have confirmed that social support was strongly positively correlated with the physiological and psychological aspects of long-term survival of cancer [51,52]. Hence, social support is an important factor to predict the quality of life of cancer patients [50]. The key factor of social support as a stress buffer is that the individual perceives that others will provide appropriate support, which will reduce the emotional and physiological reactions of individual stress.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, anxiety and depression were negatively correlated with PSS, and PSS was positively correlated with quality of life, consistent with previous ndings [49,50]. PSS moderates the effects of anxiety or depression on quality of life of patients.…”
Section: Discussionsupporting
confidence: 92%